Unveiling Seismic Patterns in Kalimantan: Insights into Earthquake Events Over the Last Two Decades (2000-2024) - Ilham Muthahhari; R. Grata Sabdo Yudhopratidino; Eva Darnila (Yayasan Kita Menulis - JoCPES, 2024)
Seismic activity in Kalimantan, once considered to be relatively minimal, has garnered increased scrutiny due to the presence of active fault lines, including the Mangkalihat, Meratus, and Tarakan faults. This research examines earthquake occurrences in Kalimantan from 2000 to 2024, utilizing seismic data from the USGS and analytical tools such as QGIS and Microsoft Excel. The findings reveal that earthquake occurrences are predominantly located in the northeastern and southeastern parts of the region, with magnitudes varying between 3.9 and 6.1. Notably, the year 2015 experienced a marked increase in seismic events. The results emphasize the critical need for disaster preparedness, the resilience of infrastructure, and the establishment of Early Warning Systems (EWS) to alleviate potential hazards. This study advocates for ongoing monitoring and enhanced public awareness to diminish seismic vulnerability in Kalimantan.